Netflix, Muslims and cultural imperialism - Mohamed, Shafizan (IIUM Today, 2020)
What do most people do when in quarantine? They watch Netflix. While most businesses are at their wits end trying to deal with the impact of the COVID-19 health crisis, Netflix is capitalising on people under lockdown.